The Matthean parables : a literary and historical commentary - Jones, Ivor H. (Novum Testamentum, Supplements, 1995)
The Matthean Parables offers a fresh approach to the origin of Matthew's Gospel. It builds on current historical, literary, rhetorical and sociological studies of Matthew's Gospel to show how the Matthean parables illuminate the structure, purpose and theology of that gospel. The first part of the book establishes the need for a new attempt to define the genre of Matthew's Gospel, examines what is meant by a parable, and summarises the contribution made by the parables to that new attempt. The second part is a thorough exegetical, historical critical and literary study of all the Matthean parables in the context of the whole gospel and in the light of all the Matthean figurative material. An appendix illustrates the use of syntactical material in defining the character and style of a biblical text.